2014
DOI: 10.5267/j.msl.2014.6.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of independent auditor's report on profit distribution policy: Evidence from Tehran Stock Exchange

Abstract: Profit distribution is one of the most debatable subjects in financial field. Opposite theoretical models that sometimes, do not have a strong empirical support look for the explanation of corporate dividend policy. In this paper, the relationship between profit sharing policy and auditor`s and managers' expected profit is studied. The study gathers the necessary information of 99 firms listed on Tehran Stock Exchange over the period 2002-2011. The implementation of regression analysis shows that there was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Puspita & Utama (2016) research has come to a similar point with Serly & Helmayunita (2018) that indicated audit fee positively and significantly affected the financial statement. Meanhile, Auliyah et al, (2022), Putri (2021) and Paydarmansh et al, (2014) argued otherwise, in which audit fee does not affect the financial statement. Based on the theories, substantive relationship and results of the previous researches above, this research proposes a hypothesis as follows:…”
Section: Audit Fee's Influence On Financial Statements Integritymentioning
confidence: 99%
“…Puspita & Utama (2016) research has come to a similar point with Serly & Helmayunita (2018) that indicated audit fee positively and significantly affected the financial statement. Meanhile, Auliyah et al, (2022), Putri (2021) and Paydarmansh et al, (2014) argued otherwise, in which audit fee does not affect the financial statement. Based on the theories, substantive relationship and results of the previous researches above, this research proposes a hypothesis as follows:…”
Section: Audit Fee's Influence On Financial Statements Integritymentioning
confidence: 99%